Controlling shareholders: issues and challenges for shareholders’ empowerment in directors’ remuneration in corporate Malaysian - Mohd. Sulaiman, Aiman @ Nariman (Monash UniversityLibrary, 2013)

(untitled)
Current reform concerning directors’remuneration relies on improvinglegal rules and self-regulation to minimise expropriation of minority share-holders. These have prominently focussed on empowering shareholders. Nonetheless, it is unclear as to the extent these reform proposals are compatible within the concentrated shareholding structure. Some of the reforms taking place in developed countries are suited for dispersed shareholding structure and thus transplanting them to emerging economies with concentrated share-holders may be ineffective. Malaysia poses an interesting case study, especially to countries with similar ownership structure as the concentrated shareholding structure raises different agency problems. The issue of protection of minority shareholder rights and the prevention of abuse of the controlling power by paying excessive remuneration to the executives is therefore a subject of due consideration in Malaysia and countries with similar shareholding structures. This article recommends that Malaysia and other emerging countries look into encouraging limited shareholder empowerment in tandem with laws.